Tabi‘in Perempuan dalam Periwayatan Hadis: Analisis Konten dan Otoritas Sanad dalam Musnad Ahmad bin Hanbal. - Riri Maiyati; Ismiati Ismiati (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2026)
This study examines the role of tabi’iyyat generation in the transmission of hadith in the Musnad of Ahmad ibn Hanbal. Through a qualitative literature review, primary data was analyzed using Krippendorff’s content analysis model and Mahmud al-Thahhan’s sanad analysis. The macro level findings successfully identified a data population of 126 tabi’iyyat. Thematically, the content of their hadith contributions is classified into the domestic sphere (43%-family relations, the role of mothers, and health), the sphere of daily worship (37%-purification, prayer, zakat,fasting, and pilgrimage), and the public sphere (20%-social ethics, maintaining social ties, and social solidarity). Meanwhile, a formal examination of the sanad criticism aspect based on a sample of 15 major hadiths revealed high validity of the evidence, with 73.3% classified as sahih, 20% as hasan, and only 6.7% as da’if. Critically, these weaknesses stem purely from the memory lapses of al-tabi’iyyun within their transmission chains, not from intellectual deficiencies in tabi’iyyat. This study concludes that tabi’iyyat possess scholarly authority equivalent to that of al-tabi’iyyun, implying a strong theological reference to support a gender-just hadith studies curriculum